Da'wah Orientation towards the Importance of Maqasid Sharia Islamic Philosophy in Indonesia - Uliyah, Taqwatul (Westscience Press, 2025)
Sadly, there are still some da'wah activities in Indonesian society that are exclusive, intolerant, and even potentially contrary to the spirit of nationalism. In 2017, the Indonesian Ulema Council issued a da'wah guidebook that was intended to be a moral standard for preachers in Indonesia. This literature review is an effort to find out whether the dimension of sharia mqasid values exists in the formulation of the da'wah orientation of the Indonesian Ulema Council. Normative-philosophical methods are used in this study. The concept of modern sharia maqasid developed by Jasser Auda serves as the basis for the analysis of this research. The results of the study show that the formulation of the da'wah orientation of the Indonesian Ulema Council contains elements of sharia maqasid values. Hifz din and hifz nafs form the personality of religious-humanist Muslims, hifz waton forms the personality of nationalist and pluralist Muslims, and hifz ummah forms the personality of prosperous and harmonious Muslims. This research shows that the value of sharia maqasid can serve as the basis for the values, methods, and paradigms of Islamic da'wah in a multicultural society. This study has not studied the concrete steps taken by the Indonesian Ulema Council to support da'wah activities in Indonesia in accordance with the various da'wah orientations that it has set.